Enantiodiscrimination of carboxylic acids using the diphenylprolinol NMR chiral solvating agents. Issue 1 (8th December 2015) - Li, Gaowei; Cao, Jiangming; Zong, Wen; Lei, Xinxiang; Tan, Renxiang
Abstract : Enantiopure diphenylprolinols have been developed as effective and practical NMR chiral solvating agents for the enantiodiscrimination of diverse α-carboxylic acids. Abstract : Enantiopure diphenylprolinols were synthesized from a commercially available starting material. The utility of 1 H NMR spectroscopy for the differentiation of enantiomers using these chiral compounds as CSAs is stated, and their capacity acting as receptors for various carboxylic acids via hydrogen bonding is exploited. A linear relationship has been observed between the experimental and observed values of ee indicating the possible use of these compounds for quick and reliable analysis of enantiomerically enriched samples of various mandelic acids. From the experiments performed a preliminary conclusion indicated that the diphenylprolinol1b with the free NH and OH is most effective in the chiral discrimination of carboxylic acids in 1 H NMR.